Controlling Quantum Cascade Laser Optical Frequency Combs through Microwave Injection. Issue 12 (11th November 2021) - Schneider, Barbara; Kapsalidis, Filippos; Bertrand, Mathieu; Singleton, Matthew; Hillbrand, Johannes; Beck, Mattias; Faist, Jérôme
Abstract: In this work, control over the precise state emitted by quantum cascade laser frequency combs through strong radio‐frequency current modulation close to their repetition frequency is demonstrated. In particular, broadening of the spectrum from about 20 cm −1 to an average bandwidth of 60 cm −1 can be achieved throughout most of the current dynamical range while preserving the coherence, as measured by shifted wave interference Fourier transform spectroscopy (SWIFTS). The required modulation frequency to achieve this broadening is red‐shifted compared to the free‐running beatnote frequency at increasing modulation powers starting from 25 dBm, whereas the range where it occurs narrows. Outside of this maximum‐bandwidth range, the spectral bandwidth of the laser output is gradually reduced and the new center frequency is red‐ or blue‐shifted, directly dependent on the detuning of the modulation frequency. By switching between two modulation frequencies detuned symmetrically with respect to the free‐running beatnote, two multiplexed spectral regions with negligible overlap from the same device at rates of at least 20 kHz can be generated. In the time‐domain, with both SWIFTS and interferometric autocorrelation (IAC) measurements a transition from quasi‐continuous output to long‐pulsed ( τ p ≈ 55 ps) output is shown by ramping up the injection power to 35 dBm. Abstract : The state of a quantum cascade laser is controlled through current modulation in the microwave region. Spectral broadening and fast switching between subsections of the spectrum, as well as changing the temporal output from quasi‐continuous to strongly modulated can be achieved. The same maximal spectral bandwidth can be reached throughout the entire dynamical range of the device.